Inovasi Cemilan Sehat dan Praktis Berbahan Alami sebagai Alternatif Jajanan Anak Sekolah - Bolivia Renata Sianipar; Grace Putri Johana Rajagukguk; Raihan Ananda Azma; Stela Triyuni Purba; Ulul Azmi Fadhilah; Fitriani Lubis (Departement of Mathematics Education, 2024)
The innovation of healthy snacks made from natural ingredients in the form of jelly with dragon fruit, strawberries, and mango aims to provide a healthy alternative for school children and the surrounding community. This snack combines the nutritional benefits of fresh fruits rich in vitamins and fiber while offering a delicious taste that appeals to children. With practical and easy-to-consume packaging, this jelly is ideal for sale in school environments and local markets, making it a healthier choice compared to processed snacks. This innovation aims to support healthy eating habits in schools and raise awareness among the community about the importance of good nutritional intake.